2016
DOI: 10.3389/fnhum.2016.00615
|View full text |Cite
|
Sign up to set email alerts
|

Sluggishness of Early-Stage Face Processing (N170) Is Correlated with Negative and General Psychiatric Symptoms in Schizophrenia

Abstract: Patients with schizophrenia consistently exhibit abnormalities in the N170 event-related potential (ERP) component evoked by images of faces. However, the relationship between these face-specific N170 abnormalities in patients with schizophrenia and the clinical characteristics of this disorder has not been elucidated. Here, ERP recordings were conducted for patients with schizophrenia and healthy controls. The amplitude and latency of the N170 component were recorded while participants passively viewed face a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 76 publications
1
17
1
Order By: Relevance
“…The subsequent researches support the hypothesis by showing white matter damages [67,[75][76][77][78], and reductions of brain network synchrony [69,[79][80][81][82][83] in people with diagnose of schizophrenia. More specifically, the abnormalities of the myelin, which could contribute to the white matter impairment, are also found to be relevant with schizophrenic symptoms [12,84,85]. These findings suggest that the deficits of synchrony between brain areas might be vital for schizophrenic psychoses.…”
Section: Do Schizophrenia and Slpe Shared Common Bio-marks?mentioning
confidence: 78%
“…The subsequent researches support the hypothesis by showing white matter damages [67,[75][76][77][78], and reductions of brain network synchrony [69,[79][80][81][82][83] in people with diagnose of schizophrenia. More specifically, the abnormalities of the myelin, which could contribute to the white matter impairment, are also found to be relevant with schizophrenic symptoms [12,84,85]. These findings suggest that the deficits of synchrony between brain areas might be vital for schizophrenic psychoses.…”
Section: Do Schizophrenia and Slpe Shared Common Bio-marks?mentioning
confidence: 78%
“…Twelve of 17 studies reported no difference in N170 latency between diagnostic groups The remaining five studies found adults with SZ showed delayed N170 latency to faces compared to TD controls. One of these studies found these results for both upright and inverted faces (Zheng et al 2016) and showed that N170 latency correlated with both negative and general . CC-BY-NC 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: N170 Latency In Sz: Facementioning
confidence: 91%
“…The methods used in the abovementioned statistical analyses have been verified by other experimental studies. [ 46 ]…”
Section: Methodsmentioning
confidence: 99%